2021
DOI: 10.1002/da.23153
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar II disorder has the highest prevalence of seasonal affective disorder in early‐onset mood disorders: Results from a prospective observational cohort study

Abstract: Background: Many mood disorder patients experience seasonal changes in varying degrees. Studies on seasonality have shown that bipolar disorder has a higher prevalence rate in such patients; however, there is limited research on seasonality in early-onset mood disorder patients. This study estimated the prevalence of seasonality in early-onset mood disorder patients, and examined the association between seasonality and mood disorders. Methods: Early-onset mood disorder patients (n = 378; 138 major depressive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…In addition, BD-2 subjects were more prone to switch from depression to elevated mood in association with antidepressant treatment, consistent with their tendency to follow a DMI course and lesser likelihood of receiving mood-stabilizing agents. BD-2 subjects were less subject to seasonal variations than BD-1 subjects, unlike findings from a smaller recent study (Yeom et al 2021 ). The greater likelihood of having a cyclothymic temperament and a rapid-cycling course along with less seasonal changes may indicate that mood oscillations are more chaotic in BD-2 vs. BD-1 subjects.…”
Section: Discussioncontrasting
confidence: 77%
“…In addition, BD-2 subjects were more prone to switch from depression to elevated mood in association with antidepressant treatment, consistent with their tendency to follow a DMI course and lesser likelihood of receiving mood-stabilizing agents. BD-2 subjects were less subject to seasonal variations than BD-1 subjects, unlike findings from a smaller recent study (Yeom et al 2021 ). The greater likelihood of having a cyclothymic temperament and a rapid-cycling course along with less seasonal changes may indicate that mood oscillations are more chaotic in BD-2 vs. BD-1 subjects.…”
Section: Discussioncontrasting
confidence: 77%
“…BD patients commonly show seasonal changes in mood, and SAD occurs more frequently in BD compared to MDD or community controls. One recent study suggested that compared to MDD and BD I, subjects with BD II were the most likely to show seasonal mood variation and disability 183 . Previous studies of seasonal BD have found association with clock gene variants.…”
Section: Resultsmentioning
confidence: 99%
“…One recent study suggested that compared to MDD and BD I, subjects with BD II were the most likely to show seasonal mood variation and disability. 183 Previous studies of seasonal BD have found association with clock gene variants. In a genetic association study of 269 BD patients (26% with SAD), the authors studied 349 SNPs and after correction for multiple testing, identified significant associations with five variants in NPAS2.…”
Section: Seasonalitymentioning
confidence: 97%
“…Seasonal changes affect all patients with mood disorders, and seasonal affective symptoms occur more frequently in BD compared to MDD or community controls. Previous studies suggested that subjects with BD II were the most likely to show seasonal mood variation and disability compared to MDD and BD I [83]. Genome-wide association studies (GWAS) observed associations between seasonal BD and clock gene variants, especially with NPAS2, CSNK1E, and RORA [84,85].…”
Section: Environmentmentioning
confidence: 99%